Conseqüências de uma tempestade geomagnética no posicionamento relativo com receptores GPS de simples freqüência - Dal Poz, William Rodrigo [UNESP]; De Oliveira Camargo, Paulo [UNESP] (My University, 2006)
The error associated with the ionosphere depends on Total Electron Content (TEC) of the ionosphere. The geomagnetic field exerts strong influence in the TEC variation, because it controls the movement of the electrons. After solar events the magnetic lines of force can be compressed, characterizing the geomagnetic storm. The aim of this paper is to present to geodesic community the effects of a geomagnetic storm in the relative positioning. The processing of the data was accomplished with an interval of two hours, with a 430 km baseline. The analyze of the obtained results have been carried out from the discrepancies between the true coordinates and corresponding ones obtained in the processing of the baseline. The used data in this paper include the period of 30/03/2001 up to 02/04/2001. In March 31 a strong geomagnetic storm happened. One day after, that it corresponds to main phase of the storm, the values of the discrepancies decreased significantly. For instance, in 01:00-03:00 UT period, the value of the planimetric discrepancy reached 20 m in the storm day. However, in the main phase of the storm, the planimetric discrepancy decreased to 0.1 m.
Consequences of a geomagnetic storm in the relative positioning with single-frequency GPS receivers
Keywords: Geomagnetic storm; GPS; Ionosphere; TEC; error analysis; geodesy; geomagnetic storm; ionosphere; positioning